(untitled) (Eurasian Journal of Humanities and Social Sciences, 2021)
This paper analyses the innovative and quite interesting methods we have in teaching English language. We may have a number of teaching methods in between traditional and modern. Everybody has their own understanding and conclusions on teaching English language. But this paper portrays combining these two types how we can make our teaching very effective. We have been completely bounded with traditional methods of teaching and understanding where the present-day learners felt uncomfortable a bit. Learner’s mind will never be static it is ever growing and ever changing. Whatever the teaching methodology can be, but teaching must be leaners centred. However, this paper scrutinizes the difference between traditional and practical teaching and thereafter learning.